Franz Schubert and his world - Gibbs, Christopher Howard; Solvik, Morten (Bard Music Festival series., 2014)
During his short lifetime, Franz Schubert (1797-1828) contributed to a wide variety of musical genres, from intimate songs and dances to ambitious chamber pieces, symphonies, and operas. The essays and translated documents in Franz Schubert and His World examine his compositions and ties to the Viennese cultural context, revealing surprising and overlooked aspects of his music. Contributors explore Schubert's youthful participation in the Nonsense Society, his circle of friends, and changing views about the composer during his life and in the century after his death. New insights are offered.